Analisis pengaruh karakteristik rumah tangga, modal manusia, modal material terhadap kemiskinan rumah tangga di 34 provinsi di Indonesia tahun 2019-2020 - Jatri Endah Nur Muliyanawati; Nasikh Nasikh (Jurnal Ekonomi, Bisnis dan Pendidikan (JEBP), 2021)
Abstract this Study aims to describe the influence of the Characteristics of the Households that consist of Per Capita Income and Number of Family Members, Human Capital consists of the Inhabitants of Using a Computer and the Status of Education, Capital of the Material, which consists of the Area of the Floor of the House and the Status of the Ownership of residential Buildings Against Poverty Households that consist of a Percentage indicator of Poor people, The Depth of Poverty, the Poverty Severity Index in 34 Provinces in Indonesia in the Year 2019-2020. The design and kinds of research used in this research is using quantitative methods. The Data in this research are secondary data by using time series data. Data collection was done by means of documentation. In this study using the method of the analysis of SEM (Structural Equation Modeling). Based on the results of the analysis show that the Characteristics of the Households that consist of Per Capita Income and Number of Family Members has no significant effect on Household Poverty. Human capital consists of the Inhabitants of Using a Computer and the Status of the Education has no significant effect on Household Poverty. Material capital which consists of the Area of the Floor of the House and the Status of Ownership of the residential Buildings have a significant effect on Poverty of the Household in the year 2019, and no significant effect in 2020. Abstrak Penelitian ini bertujuan untuk mendeskripsikan pengaruh Karakteristik Rumah Tangga yang terdiri dari Pendapatan Per Kapita dan Jumlah Anggota Keluarga, Modal Manusia yang terdiri dari Penduduk Menggunakan Komputer dan Status Pendidikan, Modal Material yang terdiri dari Luas Lantai Rumah dan Status Kepemilikan Bangunan Tempat Tinggal Terhadap Kemiskinan Rumah Tangga yang terdiri dari indikator Persentase Penduduk Miskin, Indeks Kedalaman Kemiskinan, Indeks Keparahan Kemiskinan di 34 Provinsi di Indonesia Tahun 2019-2020. Rancangan dan macam penelitian yang digunakan dalam penelitian ini yaitu menggunakan metode kuantitatif. Data dalam penelitian ini yakni data sekunder dengan menggunakan data time series. Pengumpulan data dilakukan dengan cara dokumentasi. Dalam penelitian ini menggunakan metode analisis SEM (Structural Equation Modeling). Berdasarkan hasil analisis diketahui bahwa Karakteristik Rumah Tangga yang terdiri dari Pendapatan Per Kapita dan Jumlah Anggota Keluarga tidak berpengaruh signifikan terhadap Kemiskinan Rumah Tangga. Modal Manusia yang terdiri dari Penduduk Menggunakan Komputer dan Status Pendidikan tidak berpengaruh signifikan terhadap Kemiskinan Rumah Tangga. Modal Material yang terdiri dari Luas Lantai Rumah dan Status Kepemilikan Bangunan Tempat Tinggal berpengaruh signifikan terhadap Kemiskinan Rumah Tangga pada tahun 2019, dan tidak berpengaruh signifikan pada tahun 2020.